Soil microbial activity as a biomarker of degradation and remediation processes - Pascual, J. a; Garcia, C.; Hernandez, T.; Moreno, J. L.; Ros, M. (Soil Biology and Biochemistry, 2000)
Several organic matter fractions together with biological and biochemical parameters were measured in a range of intensively farmed soils in SE Spanish Mediterranean region, which had been abandoned (i.e. not used in agriculture) for different periods of time. These soils were compared with adjacent natural soils that had never been used for agriculture. There was a general decline of total organic carbon (TOC), extractable humic substances, water-soluble carbon (WSC) and carbohydrates, microbial biomass and respiration with the time elapsed since abandonment. There was also a decline in plant cover in the abandoned soils. When a degraded soil was amended with municipal solid waste at rates of 6.5 and 26 kg m 22 as a potential means of remediation, TOC, humic substances, WSC, microbial biomass and respiration rates signi®cantly increased but only at the higher rate of amendment. Plant cover was signi®cantly enhanced by both rates of the amendments and was still present 10 years after the amendment. These data con®rm that agricultural soil abandonment leads to soil degradation and that the addition of urban waste could be a suitable technique with which to restore their quality
Keywords: dehydrogenase; hydrolases; organic matter; soil remediation

Soil microbial activity as a biomarker of degradation and remediation processes - Pascual, J.a; García, C; Hernández, T; Moreno, J L; Ros, M (Soil Biology and Biochemistry, 2000)
Several organic matter fractions together with biological and biochemical parameters were measured in a range of intensively farmed soils in SE Spanish Mediterranean region, which had been abandoned (i.e. not used in agriculture) for different periods of time. These soils were compared with adjacent natural soils that had never been used for agriculture. There was a general decline of total organic carbon (TOC), extractable humic substances, water-soluble carbon (WSC) and carbohydrates, microbial biomass and respiration with the time elapsed since abandonment. There was also a decline in plant cover in the abandoned soils. When a degraded soil was amended with municipal solid waste at rates of 6.5 and 26 kg m 22 as a potential means of remediation, TOC, humic substances, WSC, microbial biomass and respiration rates signi®cantly increased but only at the higher rate of amendment. Plant cover was signi®cantly enhanced by both rates of the amendments and was still present 10 years after the amendment. These data con®rm that agricultural soil abandonment leads to soil degradation and that the addition of urban waste could be a suitable technique with which to restore their quality
Keywords: dehydrogenase; hydrolases; organic matter; soil remediation